A new species of Oxalis sect. Thamnoxys (Oxalidaceae) from the state of Bahia, Brazil - Fiaschi, Pedro; Cabral, Fernando Santos; Lima, Duane Fernandes (Phytotaxa, 2023)
Oxalis jacobinensis, a new species of Oxalis sect. Thamnoxys, is described from the State of Bahia, in the northern sector of the Chapada Diamantina mountains. It can be distinguished from other species of the section by the leaves usually grouped at the stem apex, terminal leaflet blades rhombic-ovate to lanceolate, usually appearing grayish when fresh on the abaxial side, pedicels articulated at ca. 1/3 of their length, usually leaving a conspicuous foot, and capsules with two-seeded carpels narrowing distally, and abaxially covered with short stalked glandular hairs. We provide a description, illustrations, a geographic distribution map, a preliminary evaluation of its conservation status, and taxonomic notes.